Answer:
The function in the form of fog(x) is written as 48 x² + 336 x + 590
Step-by-step explanation:
Given function as :
f(x) = 3 x² - 6 x + 5
g(x) = - 4 x - 13
So, The function in the form of fog(x) is written as
We, substitute the value of g(x) into f(x)
∴ fog(x) = 3 (g(x))² - 6 (g(x)) + 5
Or, fog(x) = 3 (- 4 x - 13 )² - 6 ( - 4 x - 13 ) + 5
or, fog(x) = 3 (16 x² + 169 + 104 x) + 24 x + 78 + 5
or , fog(x) = 48 x² + 507 + 312 x + 24 x + 78 + 5
or , fog(x) = 48 x² + 336 x + 590
So, The function in the form of fog(x) = 48 x² + 336 x + 590
Hence The function in the form of fog(x) is written as 48 x² + 336 x + 590 Answer